TERAHERTZ TRAVELING-WAVE TUBE ON A RECTANGULAR WAVEGUIDE FOLDED IN A CIRCULAR SPIRAL - A. A. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The most promising in the THz range is traveling-wave tubes (TWTs) and backward-wave tubes (BWTs) on a serpentine-curved (zigzag-rolled) rectangular waveguide. They are implemented in the THz range (220 GHz), although their characteristics are far from satisfactory due to the strict restriction on the tape electron beam width, that does not allow reaching the summarizing beam current optimum level. To replace the zigzag convoluted waveguide with the spiraled for the TWT and BWT on a curved rectangular waveguide is the best way to remove the ribbon beam width restriction. In the early TWT and BWT design a waveguide planar spiral was also flat in the upper and lower parts connected by vertical idle (without beam) transitions. Proposed design can be significantly improved both in relation to the electron interaction process with the waveguide field and in relation to the TWT-BWT manufacturing technology if instead of a planar waveguide spiral, a circular one is used. The article proposes the TWT designing a terahertz rectangular waveguide folded as a circular spiral. The design differs from the previously proposed TWT with a planar-spiral waveguide by the improved interaction conditions between the electron beam and the waveguide field, as well as the manufacturing technology simplification for terahertz range. Based on numerical simulation, it is shown that proposed TWT achieves Gн = 42÷48 dB saturation gain in the 220 GHz range with the waveguide turn number n = 40÷50. The proposed TWT design on a rectangular waveguide folded in a circular spiral is more technologically advanced than the TWT on a planar-spiral waveguide. In the most necessary 220 GHz range the efficiency is very high and can provide the need for amplifiers and generators in this and other ranges. We also note that the TWT on a spirally folded waveguide can operate in the BWT mode and, moreover, simultaneously in the TWT and BWT modes.